Experiences of home as an aspect of well‐being in people over 80 years: A mixed method study. (23rd November 2021) - Almevall, Albin D.; Nordmark, Sofi; Niklasson, Johan; Zingmark, Karin
Abstract: Aims: To (1) describe experiences of home from a well‐being perspective, (2) describe participant characteristics and well‐being measures in relation to housing type (3) and how the aforementioned aspects may affect well‐being in very old persons. Design: Cross‐sectional, convergent parallel‐results mixed method design with semi‐structured interviews analysed by qualitative content analysis, in relation to descriptive statistics and specific well‐being outcome measures related to home. Methods: A total of 50 persons 80 years or older living in ordinary housing were interviewed (July 2017 to November 2018) about home in relation to well‐being, along with collection of participant characteristics and well‐being measures related to home. Results: Participants described how home had become increasingly important as it provided autonomy and acted as a social and occupational hub. However, autonomy was not unconditional, and home could also be perceived as a place of inactive solitude. Results were interpreted as relating to being in the margins of home and had a major impact on well‐being. Housing type seemed of importance with higher measures of well‐being for participants in single‐living housing compared with those living in apartment. Conclusion: Home is increasingly central to well‐being in old age; however, very old persons also have to relate to being physically and mentally in the margins of being able to remain in the home. These aspects of home potentially have a major impact on well‐being. Impact: As very old persons living in ordinary housing will constitute a larger segment of society in coming years, aspects of home can potentially have a considerable impact on well‐being for this age‐group. This study describes aspects of home that contribute to, or has adverse impact on well‐being. These aspects need thorough consideration in policy‐making and planning of health care that can affect experiences of home.